Responses of Above- and Belowground Carbon Stocks to Degraded and Recovering Wetlands in the Yellow River Delta - Shao, Pengshuai; Han, Hongyan; Yang, Hongjun; Li, Tian; Zhang, Dongjie; Ma, Jinzhao; Duan, Daixiang; Sun, Jingkuan (Frontiers in Ecology and Evolution, 2022)
Wetlands reserve a large amount of organic carbon (C), playing a key role in contributing global C stocks. It is still uncertain to evaluate wetland C stocks due to wetland disturbance or degradation. In this study, we performed the degraded and recovering wetlands to estimate aboveground C stocks and soil organic C (SOC) stocks at the depth of 1 m in the Yellow River Delta. Our results showed that the recovering wetland sequestered 1.67 Mg C ha–1 aboveground, approximately three times higher than those (0.56 Mg C ha–1) of degraded wetland, and recovering wetland stored more SOC of 51.86 Mg C ha–1 in the top 1 m soils, approximately two times higher than those (26.94 Mg C ha–1) of degraded wetland. These findings indicate that the transformation between degraded and recovering wetlands is associated with the conversion of wetland C sources and sinks. The shifts in aboveground C stocks and SOC stocks were mainly attributed to changed biotic (i.e., aboveground biomass and photosynthetic C) and abiotic (i.e., soil water, salinity, SOC and N contents, and SOC compounds) factors. The improved soil water, salinity, and nutrient enhance C reservoir, sequestering more C in aboveground vegetation and storing more SOC via photosynthetic C input of plant litter and root exudates in recovering wetland than in degraded wetland with poor soil conditions. The relationships among wetland C stocks, plant, and soil properties indicate plant-soil interaction driving wetland ecosystem C stocks in degraded and recovering wetlands. Our research suggests that wetland restoration highlights a positive response to “carbon neutrality” by efficiently sequestering C above- and belowground.